2018
DOI: 10.3390/resources7030053
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Challenges and Barriers to Participating in the Source Separation of Waste Program in Tabriz, Northwest of Iran: A Qualitative Study from the Citizens’ Perspective

Abstract: There are many problems with the waste management systems (WMSs) in developing countries. In order to provide applicable strategies for improving the WMSs in these countries, there is a need to identify the barriers and challenges at the community level. Our aim in the present study was to explain the challenges and barriers in front of the citizen’s participation in the Source Separation of Waste (SSW) program in Tabriz, Iran. In this qualitative research, 13 citizens were invited to participate and were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
2
12
1
1
Order By: Relevance
“…The authors formulate recommendations how to overcome these barriers. The findings of this work are similar to the observations made by Babazadeh et al [3], insofar that it is not sufficient to solely focus on technology and infrastructure, because motivational factors, knowledge and social perception also play a major role in implementing effective solid waste management and recycling schemes.…”
Section: No Title Of Publication Authors Type Of Publicationsupporting
confidence: 82%
See 2 more Smart Citations
“…The authors formulate recommendations how to overcome these barriers. The findings of this work are similar to the observations made by Babazadeh et al [3], insofar that it is not sufficient to solely focus on technology and infrastructure, because motivational factors, knowledge and social perception also play a major role in implementing effective solid waste management and recycling schemes.…”
Section: No Title Of Publication Authors Type Of Publicationsupporting
confidence: 82%
“…Table 1 shows that there are interlinkages between circular economy and renewable energy schemes. Seven out of the ten publications address solid wastes and their potential valorisation as part of circular economy schemes [3][4][5][6][7][8][9], which can be material recycling or energetic valorisation. Source-segregated waste destined for energetic valorisation is considered a source of renewable energy; four out of the seven manuscripts which address solid wastes are closely linked to renewable energy, and therefore fall into both categories of circular economy and renewable energy.…”
Section: Towards More Sustainable Urban Resource Management: Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the data's trustworthiness, the data collection process was reviewed and repeated with reference to similar previous field studies that applied an IAD framework in waste management by using qualitative methods [38,74]. In addition, after the participants' answers were processed, they were also asked to review the data (i.e., member checking to ensure credibility).…”
Section: Qualitative Datamentioning
confidence: 99%
“…However, those who were aware of the CBSWM further indicated that they were not adequately informed about the implications of combining wastes and the benefits of separation of waste at source. Previous research studies have indicated that awareness campaigns are key to a CBSWM and can have a positive impact on the community's attitudes towards waste management [5,14,53,54]. Awareness campaigns can be done through newspapers, internet, community meetings, radios and television.…”
Section: Knowledge Of a Cbswm By The Communitymentioning
confidence: 99%